THE EFFECT OF INTERNAL AUDIT ON THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE (GCG) IN PT. BANK XYZ IN SURABAYA - R. Bima Satya Wiratama; Iga Aju Nitya Dharmani (Jurnal Ekonomi, 2019)
To improve the Bank's performance, protect the stakeholder’s needs, and improving compliance with the applicable laws and generally accepted ethical values ​​in the banking industry, the Bank should conduct its operations in GCG. One of them is the assessment of the GCG’s implementation between the Internal Audit function. The research aims to determine the Internal Audit’s role in the implementation of GCG. The variable of this research is the Internal Audit (X) as an independent variable, and then implementation of GCG (Y) as the dependent variable. The research is using a simple linear regression analysis techniques to test the hypothesis. The data used in this research is primary data, where it was obtained through questionnaires. The population is 25 respondents, which means that all respondents were sampled. Respondents came from the Internal Audit Unit of PT. Bank XYZ. The Results are showing the coefficient of Internal Audit (X) on the application of GCG is 11,088 with a significance level is 0,00 < 0,05. So the null hypothesis (Ho) is rejected and then the alternative hypothesis (Ha) is accepted. In other words, it has a significant influence. Results of the test determination using the formula coefficient of determination, Internal Audit influenced 84% of GCG implementation. The rest was influenced by other factors that aren't included in this research.